Perfilagem do problema de resolução da equação da onda por diferenças finitas em coprocessador Xeon Phi - Vilela, Raphael Fernandes (2017)
Software Optimization is a promising technique to scientific computing applications, which can have calculations that may require several hours or even days. The idea of this work is to validate, using performance metrics, the optimization of a finite differences code that solve the wave equation in isotropic media (ISO) in two dimensional (2D) and also, transverse tilted isotropic (TTI) three dimensional (3D) media. The objective is to measure the number of floating point operations per second (FLOP/s) and the arithmetic intensity of the code developed with the use of the Many Integrated Cores (MIC) technology, pointing its operational limites and how near of these limits is this code.